2018
DOI: 10.1111/xen.12392
|View full text |Cite
|
Sign up to set email alerts
|

Immune molecular profiling of whole blood drawn from a non‐human primate cardiac xenograft model treated with anti‐CD154 monoclonal antibodies

Abstract: Most studies of xenografts have been carried out with complex immunosuppressive regimens to prevent immune rejection; however, such treatments may be fatal owing to unknown causes. Here, we performed immune molecular profiling following anti‐CD154 monoclonal antibody (mAb) treatment in heterotopic abdominal cardiac xenografts from α‐1,3‐galactosyltransferase‐knockout pigs into cynomolgus monkeys to elucidate the mechanisms mediating the undesirable fatal side effects of immunosuppressive agents. Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although efficacy in vivo is not reported yet, this approach holds some promises as recruiting Treg cells by intramuscular co-transplantation of islets with a plasmid encoding Treg cell specific chemokine CCL22 was efficacious in preventing graft rejection (Vågesjö et al, 2015). Some success has also been shown in xenotransplantation with blockade of the costimulatory pathway of CD40/CD154, which inhibited T cell and B cell signaling (Ock et al, 2018; Do et al, 2019). In mice treated with this approach, increased numbers of Treg cells and an elevated anti-inflammatory cytokine profile was found around a porcine islet grafts (Wu et al, 2017).…”
Section: Accessory Cell Strategies To Reduce Tissue Responsesmentioning
confidence: 99%
“…Although efficacy in vivo is not reported yet, this approach holds some promises as recruiting Treg cells by intramuscular co-transplantation of islets with a plasmid encoding Treg cell specific chemokine CCL22 was efficacious in preventing graft rejection (Vågesjö et al, 2015). Some success has also been shown in xenotransplantation with blockade of the costimulatory pathway of CD40/CD154, which inhibited T cell and B cell signaling (Ock et al, 2018; Do et al, 2019). In mice treated with this approach, increased numbers of Treg cells and an elevated anti-inflammatory cytokine profile was found around a porcine islet grafts (Wu et al, 2017).…”
Section: Accessory Cell Strategies To Reduce Tissue Responsesmentioning
confidence: 99%
“…Using an ex vivo porcine lung perfusion model, Kim et al demonstrated that aurintricarboxylic acid could attenuate hyperacute rejection by preventing coagulation perturbation and showed that pretreatment of the donor pig with 1‐deamino‐8‐D‐arginine vasopressin (DDAVP) decreased platelet activation as well as complement/coagulation activation resulting in the attenuation of systemic intravascular coagulation . Recently, Ock et al reported that GTKO pig hearts heterotopically transplanted into NHPs with anti‐CD154 Ab‐based immunosuppression survived from 11 to 24 days, and they performed molecular immunology profiling of the whole blood drawn from the recipient …”
Section: Research Activities In Xenotransplantationmentioning
confidence: 99%
“…37 Recently, Ock et al reported that GTKO pig hearts heterotopically transplanted into NHPs with anti-CD154 Ab-based immunosuppression survived from 11 to 24 days, 38 and they performed molecular immunology profiling of the whole blood drawn from the recipient. 39…”
Section: Pancreatic Islet and Cornea Xenotransplantationmentioning
confidence: 99%
“…Unfortunately, the immunosuppression regimen may be lethal, by a yet unidentified mechanism, though often linked with anti‐CD154 antibody treatment. Ock et al used a non‐human primate model (cynomolgus macaques) to evaluate the transcriptional changes prior to and after the standard immunosuppression protocol for porcine cardiac xenotransplantation (alpha‐1,3‐galactosyltransferase KO pigs). The regimen included cobra venom factor, anti‐thymocyte globulin, and rituximab, in the presence or absence of anti‐CD154 antibodies.…”
Section: Immune Suppressionmentioning
confidence: 99%